Hughes’ Types of Swear Words in the Comment Section of Harry Styles’ Instagram Post - Alhanova Seregar; Dewi Wulan Sari (Jurnal Sosial Humaniora dan Pendidikan, 2025)
Swear word refers to a term or expression that is typically seen as offensive, rude, impolite, vulgar, or profane. In this research, the researcher chose to analyze swear words found in the comment section of Harry Styles’ Instagram post, uploaded on July 15, 2023, which is used as the data source. This research aims to deepen the understanding of swear words and contribute to linguistic studies, particularly in non-standard language, by examining the types of swear words used in social media comments. This research used a descriptive qualitative method. The researcher used Hughes’ theory to find out the types of swear words. The results of this research showed six types of swear words, with a total of 31 swear words and 203 occurrences due to repetition. 3 swear words related to excrement (29 occurrences). 3 swear words related to animals (3 occurrences). 2 swear words related to personal background (4 occurrences). 7 swear words related to sex (104 occurrences). 7 swear words related to religion or oath (47 occurrences). 9 swear words related to mental illness (16 occurrences). Swear words related to mental illness are the largest in number. Meanwhile, swear words related to sex are the most dominant in terms of repetition.